Decoding Post-Viral Fatigue: The Basal Ganglia's Complex Role in Long-COVID - Thorsten Rudroff (MDPI AG, 2024)
Long-COVID afflicts millions with relentless fatigue, disrupting daily life. The objective of this narrative review is to synthesize current evidence on the role of the basal ganglia in long-COVID fatigue, discuss potential mechanisms, and highlight promising therapeutic interventions. A comprehensive literature search was conducted using PubMed, Scopus, and Web of Science databases. Mounting evidence from PET, MRI, and functional connectivity data reveals basal ganglia disturbances in long-COVID exhaustion, including inflammation, metabolic disruption, volume changes, and network alterations focused on striatal dopamine circuitry regulating motivation. Theories suggest inflammation-induced signaling disturbances could impede effort/reward valuation, disrupt cortical-subcortical motivational pathways, or diminish excitatory input to arousal centers, attenuating drive initiation. Recent therapeutic pilots targeting basal ganglia abnormalities show provisional efficacy. However, heterogeneous outcomes, inconsistent metrics, and perceived versus objective fatigue discrepancies temper insights. Despite the growing research, gaps remain in understanding the precise pathways linking basal ganglia dysfunction to fatigue and validating treatment efficacy. Further research is needed to advance understanding of the basal ganglia's contribution to long-COVID neurological sequelae and offer hope for improving function across the expanding affected population.